Human Security and Post-Disaster Trauma Healing: Enhancing Social Resilience Through Community Empowerment - Firsty Yukaputri; Almuchalif Suryo; Priyanto Priyanto (International Journal of Business and Quality Research, 2026)
Disasters generate multidimensional impacts that extend beyond physical destruction, affecting psychological well-being, social cohesion, and community resilience. This study examines the role of trauma healing in strengthening social resilience and community empowerment within post-disaster settings through the perspective of human security. The research employs a qualitative method with a case study approach supported by a systematic literature review. Data were collected from academic journals, books, institutional reports, and previous studies related to trauma healing, psychosocial recovery, human security, community empowerment, and disaster resilience. The findings indicate that post-disaster communities commonly experience fear, anxiety, emotional instability, social withdrawal, and declining social trust, all of which weaken adaptive capacity and collective resilience. Trauma healing interventions such as counseling, psychosocial support, group activities, religious approaches, and community therapy contribute significantly to restoring emotional stability and rebuilding social interaction among affected populations. Furthermore, trauma healing strengthens community empowerment by encouraging participation, rebuilding social cohesion, and increasing collective awareness regarding shared recovery responsibilities. The study also finds that psychosocial recovery contributes to adaptive capacity, community preparedness, mutual cooperation, and long-term social resilience, which are essential elements within the broader framework of human security and non-traditional security approaches. However, several challenges remain, including limited resources, lack of trained personnel, weak institutional coordination, cultural barriers, and sustainability issues in psychosocial recovery programs. The study concludes that trauma healing should be integrated into long-term disaster management and resilience strategies because psychological recovery constitutes an essential component of sustainable community resilience and societal stability in disaster-prone areas.